PENGARUH MODEL PICTURE AND PICTURE TERHADAP HASIL BELAJAR SISWA DI KELAS X SMK AL-MADANI - Patrisia Gita; Edy Tandililing; Syaiful B Arsyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstrack This study aimed to determine the effect of the application of learning model picture and picture to the students' learning outcomes on the impulse and momentum materials in the class X SMK AL-Madani Pontianak, the research form used was quasi experimental design with Nonequivalent Control Group Design. Population in this research was student of class X SMK AL-Madani Pontianak. Sampling technique used was simple random sampling technique with class X RPL as experiment class and class X TKJ-1 as control class. Data collection was done by measurement technique. The data collection tool was an essaybased learning test consisting of 5 questions with a reliability level of 0.6. Based on the result of posttest data analysis using non parametric statistic test U Mann Whitney test with α 5% obtained -Zhit ≤ -Ztab is -4,889 <-1,96. This shows that there was a difference between the students' learning outcomes of the control class and the experimental class. The result of calculation of effect size is 0,9 (31,59%) which means study model picture and picture give high influence to result of student learning. Keywords: Learning result, physics, picture and picture.